The Effect of Ratio, Issuance of Stocks and Auditors’ Quality toward the Timeliness of Financial Reporting on the Internet by Consumer Goods Sector Companies in Indonesia - Lidiyawati Lidiyawati; Ratih Wulandari (Bina Nusantara University, 2015)
This study was conducted to analyze the factors that affect the timeliness of financial reporting on the Internet in the Consumer Goods sector companies listed in Indonesia Stock Exchange (IDX). Variables used were leverage, profitability, size of company, the issuance of stock and the quality of auditors. Data analysis method used was logistic regression at the 0.05 level. The data used were secondary data and using sample Consumer Goods companies listed in the Indonesia Stock Exchange in 2010-2012. This study tested the effect of variable leverage, profitability, firm size, auditor quality stocks, and the timeliness of financial reporting on the Internet. The results obtained from these tests support the timeliness of audit quality of financial reporting on theInternet. However, other variables such as leverage, profitability, firm size, stock issuance did not support the timeliness of financial reporting on the Internet.